Misi di Keuskupan Surabaya: Sebuah Rancang Bangun Misi Masa Depan - Widyarto , Agustinus; Prayidno, Iswadi (Perspektif, 2009)
Living in one of the main economic centres in Indonesia, the Catholic Church of Surabaya (Surabaya Diocese) has to face all sorts of secularization. This situation has forced the diocese to redefine its role in this secularized society. The authors highlight four main concerns as the background of the discussion, i.e. (1) the globalized urban culture, (2) the role as economic centre for East Indonesia, (3) the religious diversity and (4) the crisis of identity of Catholic education. This situation leads to a major step of renewing the diocese mission strategy. While acknowledging the main stream of the mission the global church as a basis, the authors suggest two things. The first is to renew internal resources and to strengthen the internal communion. The second is to open up the church to the society by being involved in social struggle, such as promoting dialogue between religions, promoting process of inculturation, advocating the poor and the marginalized people and actively participating in social communication.